Characterization of Covering Dimension - Hasan Hajee, Nedaa (University of Thi-Qar Journal of Science, 2017)
The present study focus and define a new kind of covering dimension and show some relations with other concepts using the ( ) sets in topological space. The current paper obtain some properties and characterization of this covering dimension.